Pengawasan Penyelenggaraan Pemilu Oleh Lembaga Bawaslu: Studi Kasus Pelanggaran Pemilu Kota Pontianak Tahun 2024 - Sabrina, Vania Vinka; Akhdan, Defa; S, Setiawan; Uddarajat, Rahmansyah Rafi’; Fauzi, Rezha; Darmawan, Ivan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Based on data from Bawaslu RI in 2024, there were many violations that occurred in the election process. This shows that there are still widespread cases of election violations occurring in Indonesia. Therefore, supervision in the implementation of elections is a very important thing to do. Bawaslu carries out supervision from the national to district/city levels. If we talk about government supervision, especially election supervision in Pontianak City, there is one case related to violations of the election process. Bawaslu's role in terms of supervision is important in supervising the implementation of elections and implementing effective prevention strategies to avoid potential election violations. This research uses a literature study approach to understand the implementation of supervision in depth through existing literature. The aim of the research is to find out more about the violations that occurred in the 2024 Election in Pontianak City, the challenges faced and the prevention efforts carried out by Pontianak City Bawaslu. The research results found that there were indications of violations of Law Number 7 of 2017, especially Article 202 which broadly regulates the obligation of every voter to be registered in the administrative area where they live. The time required to uncover the problems that occur is a challenge for Bawaslu. Bawaslu's efforts to increase community participation and use of technology are key factors in maintaining the quality and credibility of elections in Pontianak City.